Word Splash Strategy in Reading Comprehension Class - Rekha Asmara; Dewi Sartika (Jurnal Bahasa dan Sastra, 2020)
Abstract: Today, technology and literacy in the area of education 4.0 has increasingly been used in many language classes. The changes in literacy conception demands the capabilities of teachers and students in utilizing digital tools in the classroom activities. Computer as one of the digital tools offers teachers some new interesting strategies for teaching reading com- prehension. Unfortunately, to comprehend a reading text in English is not easy. Many students face some problems in comprehending a text. They need to read many times to comprehend the text. The problem in reading comprehension does not only derive from students, but it is also influenced by teachers’ teaching methods or strategies, and the quality of the teachers them- selves. Moreover, reading without interest can inhibit readers to comprehend the texts well. Thus, Word Splash strategy is believed as one of the strategies that can decrease the student’s problem in comprehending the content of the text and eventually make students love reading. Keywords: education 4.0, digital tools, word splash strategy Abstrak: Saat ini, teknologi dan literasi di era Pendidikan 4.0 telah digunakan dalam kelas-ke- las pembelajran Bahasa. Perubahan terhadap konsep literasi meminta guru dan siswa untuk memaksimalkan perangkat digita dalam kegiatan kelas. Komputer sebagai salah satu alat yang menawarkan berbagai strategi baru kepada guru untuk mengajarkan pemahaman memba- ca. Sayangnya, untuk memahami teks bacaan Bahasa Inggris tidaklah mudah. Banyak siswa meng¬hadapi banyak basalah dalam memahami isi bacaan. Mereka perlu membca teks be- rulang-ulang demi mahami bacaannya. Masalah dalam memahami bacaan ini tidak hanya diala- mi oleh siswa saja, namun juga dipengaruhi oleh metode dan strategi mengajar guru, dan kual- itas guru terse¬but. Terlebih lagi, membaca tanpa diiringi dengan minat, dapat mempengaruhi pemahaman siswa terhadap teks tersebut. Sehingga, Word Splash Strateg dipercaya sebagai salah satu strate¬gi yang dapat mengurasi permasalahan siswa dalam memahami konten bacaan dan membuat siswa menyukai kegiatan membaca. Kata-kata kunci: pendidikan 4.0, perangkat digital, word splash strategi